Natural history of chronic HBV infection in West Africa: a longitudinal population-based study from The Gambia. Issue 12 (16th July 2015) - Shimakawa, Yusuke; Lemoine, Maud; Njai, Harr Freeya; Bottomley, Christian; Ndow, Gibril; Goldin, Robert D; Jatta, Abdoulie; Jeng-Barry, Adam; Wegmuller, Rita; Moore, Sophie E; Baldeh, Ignatius; Taal, Makie; et al.
Abstract : Background: The natural history of chronic HBV infection in sub-Saharan Africa is unknown. Data are required to inform WHO guidelines that are currently based on studies in Europe and Asia. Methods: Between 1974 and 2008, serosurveys were repeated in two Gambian villages, and an open cohort of treatment-naive chronic HBV carriers was recruited. Participants were followed to estimate the rates of hepatitis B e (HBeAg) and surface antigen (HBsAg) clearance and incidence of hepatocellular carcinoma (HCC). In 2012–2013, a comprehensive liver assessment was conducted to estimate the prevalence of severe liver disease. Results: 405 chronic carriers (95% genotype E), recruited at a median age of 10.8 years, were followed for a median length of 28.4 years. Annually, 7.4% (95% CI 6.3% to 8.8%) cleared HBeAg and 1.0% (0.8% to 1.2%) cleared HBsAg. The incidence of HCC was 55.5/100 000 carrier-years (95% CI 24.9 to 123.5). In the 2012–2013 survey (n=301), 5.5% (95% CI 3.4% to 9.0%) had significant liver fibrosis. HBV genotype A (versus E), chronic aflatoxin B1 exposure and an HBsAg-positive mother, a proxy for mother-to-infant transmission, were risk factors for liver fibrosis. A small proportion (16.0%) of chronic carriers were infected via mother-to-infant transmission; however, this population represented a large proportion (63.0%) of the cases requiring antiviral therapy. Conclusions: The incidence of HCC among chronic HBV carriers in West Africa was higher than that in Europe but lower than rates in East Asia. High risk of severe liver disease among the few who are infected by their mothers underlines the importance of interrupting perinatal transmission in sub-Saharan Africa.